PD-L1 testing in advanced stage lung cancer using cytology samples: Suitability and reporting issues. Comparison between two tertiary referral centers - Elshiekh Mohamed; Spinelli Manuela; Iles Sandra; Hopcroft Danielle; Trivedi Pritesh; Gupta Nandita; Bhagwat Priya; Viola Patrizia (Annals of Cytology and Pathology - Peertechz Publications, 2021)
Background: Lung cancer is the most common cause of cancer-related death worldwide and unfortunately up to 80% of patients amongst newly diagnosed are inoperable therefore the cytological sample is often the only material available for diagnosis and assessment of molecular characteristics driving the treatment. Recently immunotherapy has shown promising results in tumors expressing Program Death Ligand 1 (PD-L1). The expression of PDL1 can routinely be detected by immunohistochemistry. However, the presence of several antibodies with different cut-off and the expression of this marker by normal immune cells are generating confusion in interpretation and the need for harmonization amongst pathologists. Materials and methods: We assessed the suitability of 74 consecutive cell blocks from cytology samples for PDL1 testing and evaluate the concordance between two different antibodies (Ventana assay SP263 and Dako 223C pharmDx assay) and amongst different pathologists from two different tertiary referral center for thoracic pathology. The degree of agreement was measured by Fleiss K statistic (FKS) for categorical scores after dichotomization based on specified cutoffs. A review of discordant cases was also performed. Results: Review of the slides stained with both antibodies showed substantial agreement within our department and moderate agreement with results from the other institution. Overall less than 10% of cases were deemed inadequate. Discordant cases showed a decreased amount of tumor cells, therefore, tumor heterogeneity could be responsible for the variation in the reading.  Conclusions: Our results show overall concordance between the two antibodies and the suitability of cytology material for PDL-1 testing.